2021
DOI: 10.1080/15476286.2021.1983288
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed RNA editing: recent advances and open challenges

Abstract: RNA editing by cytosine and adenosine deaminases changes the identity of the edited bases. While cytosines are converted to uracils, adenines are converted to inosines. If coding regions of mRNAs are affected, the coding potential of the RNA can be changed, depending on the codon affected. The recoding potential of nucleotide deaminases has recently gained attention for their ability to correct genetic mutations by either reverting the mutation itself or by manipulating processing steps such as RNA splicing. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 91 publications
0
28
0
Order By: Relevance
“…Current study, reported many RESs, and the statics of altering types demonstrated that RE normally happens as G-A, T-C, C-U, and A-I changes in deciphered areas of cellular organs mRNAs. We found that changes in coding regions of the proteins were found at third and first positions which changed the physiochemical properties of the amino acids ( Khosravi and Jantsch, 2021 ; Din et al, 2022 ). Most of the amino acids were changed to hydrophobic which are agreement to the previous research ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…Current study, reported many RESs, and the statics of altering types demonstrated that RE normally happens as G-A, T-C, C-U, and A-I changes in deciphered areas of cellular organs mRNAs. We found that changes in coding regions of the proteins were found at third and first positions which changed the physiochemical properties of the amino acids ( Khosravi and Jantsch, 2021 ; Din et al, 2022 ). Most of the amino acids were changed to hydrophobic which are agreement to the previous research ( Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to dCas13-ADAR2 DD RNA-editing systems, other RNA-editing systems are currently being actively developed, such as BoxB-λN-ADAR DD , SNAP-tag-ADAR DD , and MCP-MS2-ADAR DD , in which the binding of ADAR DD and gRNA is implemented by the λN peptide, SNAP-tag protein, and MS2 bacteriophage coat-binding protein, respectively ( Fry et al, 2020 ; Khosravi and Jantsch, 2021 ). BoxB-λN-ADAR DD has manifested greater efficiency of editing of point mutations in Mecp mRNA in vivo (∼50%) and in vitro (∼70%) ( Sinnamon et al, 2017 ; Sinnamon et al, 2020 ).…”
Section: Site-directed Rna Base Editing For Monogenic-disease Therapymentioning
confidence: 99%
“…Since inosine is interpreted as guanosine due to its hydrogen bonding with cytidine, this modification introduced by ADARs can change codon meaning. [1][2][3] Two ADAR genes encode catalytically active ADARs in humans (ADAR encoding ADAR1 proteins and ADARB1 encoding the ADAR2 protein). 4 ADAR1 is expressed in two protein isoforms (p110 and p150) that differ in their N-terminal structures.…”
Section: Introductionmentioning
confidence: 99%
“…5 Because ADARs require duplex structure for activity, their reaction can be directed to specific adenosines in different transcripts using complementary guide strands which form duplexes at the target sites. 1 This approach is currently being pursued to develop therapeutic guide strands that recruit ADARs to correct disease-causing mutations in RNA. [6][7][8][9][10][11][12] One promising variation on this strategy uses chemically modified oligonucleotides to recruit endogenously expressed human ADARs for directed RNA editing.…”
Section: Introductionmentioning
confidence: 99%